The effect of early confirmation of hearing loss on the behaviour in middle childhood of children with bilateral hearing impairment - Stevenson, Jim (Blackwell Publishing Ltd, 2011)
AIM: To determine if the benefit of early confirmation of permanent childhood hearing impairment (PCHI) on children’s receptive language development is associated with fewer behavioural problems. METHOD: Follow-up of a total population cohort of 120 children with PCHI of moderate or greater severity (≥40 decibels relative to hearing threshold level) (67 males, 53 females; mean age 7y 11mo, range 5y 5mo–11y 8mo) and 63 hearing children (37 males, 26 females; mean age 8y 1mo, range 6y 4mo–9y 10mo). The main outcome measures were the Strengths and Difficulties Questionnaire (SDQ) completed by teachers and parents and the Vineland Adaptive Behaviour Scales (VABS) which are completed on the basis of a parental interview. RESULTS: Children with PCHI had lower standard scores than hearing children on the Daily Living Skills (p=0.001) and the Socialisation (p=0.001) scales of the VABS. They had significantly higher Total Behaviour Problem scores on the parent-rated (p=0.002) and teacher-rated SDQ (p=0.03). Children for whom PCHI was confirmed by 9 months did not have significantly fewer problems on the behavioural measures than those confirmed after that age (p=0.635 and p=0.196). INTERPRETATION: Early confirmation has a beneficial effect on receptive language development but no significant impact in reducing behavioural problems in children with PCHI.